Constructing a multi-bishelled cobalt-based electrocatalyst for the oxygen evolution reaction in CO₂ electrolysis - Zhang, Yu (2023)
Electrochemical reduction of CO2 into value-added chemicals has been envisioned as a promising strategy to alleviate the issue of increasing CO2 emissions. However, the sluggish oxygen evolution reaction (OER), as the anodic reaction, typically consumes approximately 90% of the electricity input, necessitating the development of an efficient OER for energy-saving purposes. Herein, we developed a unique heterostructure of multi-double (bi)-shelled Co-based spheres via a facile template-free method, in which each bi-shelled structure is composed of Co9Se8/Co9S8/CoO (Co-S-Se) with a symmetric configuration. These heterogeneous nanospheres possess both sufficient heterointerfaces and a high density of active sites and exhibit excellent OER activity in alkaline media with a low overpotential of 226 mV at 10 mA cm−2, a small Tafel slope of 46.5 mV dec−1, and long-term durability over 15 h. As a proof and concept, when coupled with a cathodic CO2 reduction reaction, the electrochemical performance of Pd nanosheets (NSs) for CO2 reduction can be significantly enhanced in terms of product selectivity and energy input. Our study might provide insight into the development of efficient OER electrocatalysts for practical CO2 reduction reactions.